Effects of bioactive peptides from black-bone chicken on blood biochemical parameters and histopathology in diabetic mice - GE Ying; ZHANG Lei; WANG Huanhuan; LOU Lifeng; LI Qinghai; HUANG Qin; ZHANG Xuedong (浙江大学学报. 农业与生命科学版)
In order to observe the effects of bioactive peptides from black-bone chicken on diabetic mice, the peptide was extracted from the breast muscles of black-bone chicken, through the steps of enzymolysis, centrifugation, ultrafiltration and freeze-drying, whose molecular mass is less than 5 kDa. Then the diabetic mice induced by streptozotocin (STZ) were randomly divided into low-dose, high-dose, drug and positive control groups (n=10), fed with 100 mg/kg bioactive peptide, 400 mg/kg bioactive peptide, 30 mg/kg acarbose and saline placebo, respectively. Besides, the normal control group was set and fed with saline. The initial body mass, fasting blood glucose level, and the final body mass, biochemical parameters after 30 d of continuous feeding were measured. Meanwhile, the pathological changes were observed. The results showed that at the end of the experiment, the body mass of positive control group decreased significantly (P＜0.05), whereas those of the other four groups increased. Compared with the positive control group, the low-dose, high-dose and drug groups had lower final fasting blood glucose levels (high-dose and drug groups, P＜0.05), lower total cholesterol level and low density lipoprotein cholesterol level, but higher high density lipoprotein cholesterol level (high-dose group, P＜0.05); higher superoxide dismutase activity, but lower malondialdehyde content (high-dose group, P＜0.05). In the low-dose, high-dose and drug groups, insulin level and islet area were significantly higher than those in the positive control group (P＜0.05); their liver and renal indexes were higher than those in the normal control group, but the pathological changes such as cell swelling and vacuolation were less than those in the positive control group. In conclusion, bioactive peptides from black-bone chicken have certain effects on hypoglycemia, hypolipidemia and tissue-protection of the pancreas, liver and kidney. In addition, the feeding dose of 400 mg/kg has better effect than that of 100 mg/kg.